2002
DOI: 10.1007/s00280-002-0432-8
|View full text |Cite
|
Sign up to set email alerts
|

A protein kinase C inhibitor induces phenotypic reversion of ras -transformed pancreatic cancer cells and cooperatively blocks tumor cell proliferation with an anti- ras peptide

Abstract: CGP 41 251 strongly blocks growth of ras-transformed pancreatic cancer cells by causing cell death and by induction of phenotypic reversion. The enhancement of this effect by the ras-p21 96-110 peptide indicated synergy between it and CGP 41 251, allowing it to block proliferation of the transformed cells selectively. These findings suggest the possibility of using these two agents in anticancer therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…In addition, PKCα has been attributed to induce drug resistance of pancreatic cancer cells [9]. In line with this, treatment with staurosporine blocked pancreatic cancer cell proliferation and reverted Ras-mediated transformation [10]. However, there are other reports showing that activation of PKCα inhibits the proliferation of pancreatic cancer cell lines [11] and increases the expression of pro-apoptotic proteins [12].…”
Section: Approaches To Target Classical Protein Kinase C (Cpkc) Subtymentioning
confidence: 99%
“…In addition, PKCα has been attributed to induce drug resistance of pancreatic cancer cells [9]. In line with this, treatment with staurosporine blocked pancreatic cancer cell proliferation and reverted Ras-mediated transformation [10]. However, there are other reports showing that activation of PKCα inhibits the proliferation of pancreatic cancer cell lines [11] and increases the expression of pro-apoptotic proteins [12].…”
Section: Approaches To Target Classical Protein Kinase C (Cpkc) Subtymentioning
confidence: 99%
“…Earlier studies demonstrated that PDAC cell lines express multiple PKCs, including α, β, ε and η [1214]. Furthermore, a number of reports indicate an important role of PKCs in promoting proliferation and in preventing apoptosis of pancreatic cancer cells [12, 1416] though a different view was also expressed [17]. A recent study demonstrates that atypical PKCι is required for the transformed growth of PDAC cells in vitro and their tumorigenesis in vivo [18].…”
Section: Protein Kinase C (Pkc) Isoforms and Pancreatic Ductal Adementioning
confidence: 99%
“…Earlier studies demonstrated that PDAC cell lines express multiple PKCs, including α, β, ε, and η (Denham et al, 1998; Guha et al, 2002; Ishino et al, 2002). Furthermore, a number of reports indicate an important role of PKCs in promoting proliferation and in preventing apoptosis of PDAC cells (Denham et al, 1998; Trauzold et al, 2001; Ishino et al, 2002; Way et al, 2002; Guha et al, 2003) though a different view was also expressed (Detjen et al, 2000). A recent study demonstrated that atypical PKCι is required for the transformed growth of PDAC cells in vitro and their tumorigenesis in vivo (Scotti et al, 2010).…”
mentioning
confidence: 99%